2007
DOI: 10.1021/ac070549h
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Process Analytical Technology System in a Freeze-Drying Process Using Raman Spectroscopy for In-Line Process Monitoring

Abstract: The aim of the present study was to propose a strategy for the implementation of a Process Analytical Technology system in freeze-drying processes. Mannitol solutions, some of them supplied with NaCl, were used as models to freeze-dry. Noninvasive and in-line Raman measurements were continuously performed during lyophilization of the solutions to monitor real time the mannitol solid state, the end points of the different process steps (freezing, primary drying, secondary drying), and physical phenomena occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 35 publications
4
121
0
1
Order By: Relevance
“…Moreover, a small peak at 9.90°, selective for δ-mannitol, in the diffractograms of runs 5, 12, 13, 18 and 19 indicated a significant residual percentage of δ-mannitol in these samples [21,22,30,34,36,37]. The overall lower intensity of the peaks in the diffractograms of the granules was attributed to a different crystal habit of the granules in comparison to the reference materials (powders) [38].…”
Section: Solid State Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, a small peak at 9.90°, selective for δ-mannitol, in the diffractograms of runs 5, 12, 13, 18 and 19 indicated a significant residual percentage of δ-mannitol in these samples [21,22,30,34,36,37]. The overall lower intensity of the peaks in the diffractograms of the granules was attributed to a different crystal habit of the granules in comparison to the reference materials (powders) [38].…”
Section: Solid State Characterizationmentioning
confidence: 95%
“…Magnesium stearate (Fagron, Waregem, Belgium) was used as lubricant for tableting. Raman spectra of reference materials of α-, β-and δ-mannitol were adopted from De Beer et al [30].…”
Section: Methodsmentioning
confidence: 99%
“…Raman spectroscopy was applied to describe mannitol polymorphic forms for instance [12], and on-line measurements during freezedrying have been performed [13,14]. NIR has also been applied for on-line freeze-drying measurements [15] and the NIR spectra of a-, b-and d-mannitol as well as mannitol hemihydrate have been reported [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy was applied to describe mannitol polymorphic forms for instance [12], and on-line measurements during freezedrying have been performed [13,14]. NIR has also been applied for on-line freeze-drying measurements [15] and the NIR spectra of a-, b-and d-mannitol as well as mannitol hemihydrate have been reported [9,13]. The potential of NIR to detect various forms is highly relevant for the quality assurance of lyophilised mannitol products as it has been shown that the freeze-drying conditions can influence the solid state form in the product [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not surprising that several models can be found in the literature describing the use of NIR for the determination of water in freezedried products. Though usually the final product is characterised, the use of both Raman and NIR spectroscopy for in-line spectroscopic measurements during freeze-drying has recently been described [7][8][9].…”
Section: Introductionmentioning
confidence: 99%